Relay co-ordination optimization for integrated solar photo-voltaic power distribution grid. Issue 1 (1st January 2019) - Shrivastava, Aayush; Saini, Devender Kumar; Pandit, Manjaree
Abstract: Distributed generation (DG) specifically from solar energy is gaining much attention. Integration of solar photo-voltaic plant (SPP) on distribution grid increases flexibility of the system but lacking behind in terms of convention protection scheme. The impact of orientation of point of common coupling (PCC) of SPP on distribution grid changes the entire power flow computation and hence, coordination of protection devices. This paper presents the power flow computation on modified IEEE 4-bus system for different integrated positions of SPP. Further analysis is carried for the fault current level with different locations and number of SPP DG. It has been found that DG integration increases the magnitudes of fault current; hence, it will have impact on relay co-ordination. A MATLAB/Simulink model is proposed for relay mis-coordination and optimal co-ordination by implementing evolutionary optimization technique. The Proposed study on IEEE 4-bus system along with three units 100 kW capacity of SPP is used to derived optimal co-ordination solution which validates the obtained results on electrical transient's analysis programming platform (ETAP).